2021
DOI: 10.1039/d1nr02872c
|View full text |Cite
|
Sign up to set email alerts
|

Improving the knock-in efficiency of the MOF-encapsulated CRISPR/Cas9 system through controllable embedding structures

Abstract: Appropriate tuning of robust artificial coatings can not only enhance intracellular delivery, but also preserve the biological functions of genetic molecules in gene based therapies. Here, we report a strategy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Reproduced from Ref. [99] with permission from the Royal Society of Chemistry delivery of plasmids to nuclei. The paxillin gene was correctly inserted in U2OS human osteosarcoma epithelial cells.…”
Section: Ph-responsive Crispr-cas9 Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced from Ref. [99] with permission from the Royal Society of Chemistry delivery of plasmids to nuclei. The paxillin gene was correctly inserted in U2OS human osteosarcoma epithelial cells.…”
Section: Ph-responsive Crispr-cas9 Deliverymentioning
confidence: 99%
“…The imidazolyl protonation in endo/lysosomes with low pHs after internalization led to effective endo/lysosomal escape of CC-ZIFs, promoting Cas9 and sgRNA delivery to nuclei for effective knocking down of gene expression by 37% over 4 days in Chinese hamster ovary (CHO) cells. Liu et al [ 99 ] also reported ZIFs for the delivery of CRISPR-Cas9 plasmid together with a paxillin donor template for knock-in of the paxillin gene (Fig. 2 B).…”
Section: Introductionmentioning
confidence: 98%
“…Cellpro-ro, Roche, Basel, Switzerland) was added and incubated for another 4 h. Then, absorbance was measured at 450 nm and 600 nm using a multimode plate reader (Infinite M1000 Pro, Tecan, NC, United States). 23). Eight-week-old male C57BL/6 mice (weight: 23 ± 2 g) were obtained from the Laboratory Animal Center of Zhe-jiang University.…”
Section: Conjugation Of Nanocomposites With Cd4abmentioning
confidence: 99%
“…Rationally designed nanomaterials can encapsulate payloads, such as drugs and biomolecules and facilitate their targeted delivery to treat various diseases [20][21][22][23][24]. We hypothesize that this technology is also applicable for delivery of immunosuppressive drugs in organ transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been developed to overcome this limitation, such as an in situ strategy that combines the synthesis of MOFs and the encapsulation of target molecules in one pot. 19,35–37 Although this system exhibits superior performance by not releasing drugs under physiological conditions in circulation, the synthesis process puts forth demanding requirements in terms of pH value, temperature, and solvent; besides, any change in the reaction conditions or drugs may cause unsuccessful encapsulation. 38 Apart from the one-pot synthesis strategy, hollow or hierarchical structures are also introduced into MOFs.…”
Section: Introductionmentioning
confidence: 99%